PENINGKATAN KUALITAS DAN KUANTITAS HAFALAN AL-QUR’AN DENGAN MANAJEMEN WAKTU - Rahman, M Abd; Kabibuloh, Nur; Naufal Alwan, Muhamad; Arrahmah, Afifah (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2024)
The problem frequently faced by students participating in tahfiz programs is allocating time between memorization and other activities. This research investigates how Quran memorizers (all of whom are school students) allocate their time for memorization, revising memorized portions to prevent forgetting and fulfilling their school and pesantren obligations. The research methodology employed is field research with a survey approach. Data collection was carried out through observation, in-depth interviews, and the use of questionnaires with 23 samples of students participating in this program. The findings of this research indicate that, in terms of the quality of memorization, 91% recited their memorization without referring to the Quran (bil ghaib) in front of other students. Regarding the increase in the quantity of memorization, it was found that 78% still have sufficient time to add new memorizations despite engaging in other activities at the pesantren. Furthermore, this research supports the assertion that having good time management can enhance Quranic memorization both qualitatively and quantitatively, even while engaging in other activities besides memorization